Basic Competencies of Disaster Nurses: A Scoping Review - Yoesra, Alfien; Susilo, Cipto (International Journal of Health and Information System, 2025)
Disaster is an event that harms various aspects such as physical, economic and infrastructure. Emergency nurses have an important role in disaster management in the mitigation, preparedness, response and rehabilitation phases. Nurses involved in the disaster management process, especially in the response phase, must have specific skills in handling mass casualties in a disaster emergency. The purpose of writing this article is to find out what basic competencies must be possessed by nurses as a team in a disaster. The method in writing this article uses a scoping review consisting of; 1) deter-mining research questions, 2) searching for relevant articles, 3) selecting ar-ticles included in the review process, 4) mapping data, 5) compiling, summa-rizing and reporting results. Analysis of research data using thematic anal-yses. The results of the study found four themes, namely; 1) one-command nurse communication in a disaster area, 2) nurse preparedness before and af-ter a disaster, 3) nurses' sensitivity to ethics and culture in dealing with dis-aster victims, 4) having skills in disaster triage, basic first aid and basic life support for victims on disaster.